Effects of ecological restoration on soil biogenic elements and their ecological stoichiometry in the Yellow River Delta, China - Li, Dongxue; Li, Yi’na; Xie, Yiliang; Cui, Baoshan; Ning, Zhonghua; Zhang, Shuyan; Bi, Zhenggang; Fu, Shouqiang; Che, Chunguang (Frontiers in Marine Science, 2022)
Coastal wetlands serve as sources and sinks of carbon, nitrogen, phosphorus, and sulfur, and their ecological stoichiometry intuitively indicates the biogeochemical cycle process of the region. This study investigated the changing trend of the soil nutrient content of soil organic carbon (i.e., SOC), total nitrogen (i.e., TN), total phosphorus (i.e., TP), and total sulfur (i.e., TS) and their ecological stoichiometric ratios in 2019-2021 in the Yellow River Delta (including north and south banks) under the Internationally Important Wetland Biodiversity Conservation Project by conducting field surveys and experiments. The results showed that SOC, TN, and TP showed the highest contents in the North Unrestoration, while the TS contents appeared highest in the North restored. Ecological restoration reduced the contents of SOC, TN and TP while increasing the content of TS. In addition, ecological restoration improved the biogenic element stability in both banks and improved the stability of ecological stoichiometry on the north bank while decreasing the ecological stoichiometry stability on the south bank. Notably, ecological restoration changed the wetland ecosystem from the perspective of soil C/S. Furthermore, the biogenic elements SOC and ecological stoichiometry C/N and C/S in the Yellow River Delta are more sensitive to environmental change due to their high ratio. Over the three years from 2019 to 2021, the contributions of soil moisture content, soil salinity, and pH to soil nutrient content and their stoichiometric ratios were 32.20%, 49.30%, and 18.50% on the north bank, respectively, and 85.70%, 8.50%, and 5.80% on the south bank, respectively. This study implies that ecological restoration generally had a positive effect on the soil contents and biological stoichiometry in the Yellow River Delta and provides a reference for future delta restoration.